The Use of Teaching Media in Arabic Language Teaching During Covid-19 Pandemic - Ahmadi, Ahmadi; Ilmiani, Aulia Mustika (IAIN Samarinda, 2020)
The characteristic of Arabic Language which is unique and different compared to other foreign languages, has become certain issue for academic society, especially with this actual condition of COVID-19, it gives impact to both teachers and students. In university level, more specifically, in order to maintain teaching – learning process to be held, various kind of media are used to support the teaching and learning activities. This research aims for exploring and describing Arabic language teaching – learning online activities in IAIN Palangka Raya using qualitative method and case study. Data collecting methods used in this research are observations, interview and documentation. Research result shows that Arabic language teaching – learning online activities in IAIN Palangka Raya adopting online technology with platforms which based on social media and e-learning application. Those platforms are categorized into three: 1) WhatsApp Group, used for intensive communications between teacher and students related to teaching – learning activities; 2) Google Classroom, used for collecting assignments; and 3) Zoom Cloud Meeting, used for audio-visual media for learning topics which need significant explanation. These medias are used after consideration on ease of accessibility, hardware compatibility, communication features, process and cost needed to use them. The findings of this research describe that Arabic language teaching – learning online activities in IAIN Palangka Raya collaborate those three aforementioned applications so that creativity, innovation and motivation are growing even during Covid-19 pandemic situation.